Neurological complications of sepsis. Issue 2 (15th April 2023) - Piva, Simone; Bertoni, Michele; Gitti, Nicola; Rasulo, Francesco A.; Latronico, Nicola
Abstract : Purpose of review: Sepsis, defined as life-threatening organ dysfunction caused by a dysregulated host response to infection, is a leading cause of hospital and ICU admission. The central and peripheral nervous system may be the first organ system to show signs of dysfunction, leading to clinical manifestations such as sepsis-associated encephalopathy (SAE) with delirium or coma and ICU-acquired weakness (ICUAW). In the current review, we want to highlight developing insights into the epidemiology, diagnosis, prognosis, and treatment of patients with SAE and ICUAW. Recent findings: The diagnosis of neurological complications of sepsis remains clinical, although the use of electroencephalography and electromyography can support the diagnosis, especially in noncollaborative patients, and can help in defining disease severity. Moreover, recent studies suggest new insights into the long-term effects associated with SAE and ICUAW, highlighting the need for effective prevention and treatment. Summary: In this manuscript, we provide an overview of recent insights and developments in the prevention, diagnosis, and treatment of patients with SAE and ICUAW.